Expression of chromogranin A-derived antifungal peptide CGA-N12 in Pichia pastoris. Issue 1 (1st January 2020) - Li, Xiaohua; Fan, Yong; Lin, Qiong; Luo, Jianxiong; Huang, Yide; Bao, Yuwang; Xu, Liyu
ABSTRACT: The human chromogranin A-derived peptide CGA-N12, which is composed of 12 amino acid residues with the sequence ALQGAKERAHQQ, showed strong antifungal activity and the least hemolytic activity in previous studies. However, synthetic peptides are relatively expensive to produce. Recombinant expression of peptides in the host cells, such as bacteria or yeast, can fastly provide cost-efficient products of peptides. Here, we developed an innovative system to produce CGA-N12 peptides in the yeast Pichia pastoris GS115 using genetic engineering technology. In order to directly secret short CGA-N12 peptides into the culture media from GS115 cells and enhance its expression effect, the structure of the CGA-N12 coding sequence was designed to mimic that of native α-factor gene of Saccharomyces cerevisiae . Four long primer pairs with sticky end were used to synthesize CGA-N12 expression sequence which contains four copies of CGA-N12 flanked by a Lys-Arg pair and two Glu-Ala repeating units. Endogenous proteases Kex2 and Ste13 in Golgi apparatus recognize and excise Lys-Arg and Glu-Ala pair to release short CGA-N12 peptides from the tandem repeat sequences, respectively. The CGA-N12 peptides were successfully expressed in Pichia pastoris with a yield of up to 30 mg/L of yeast culture as determined using HPLC. Our study indicated that the strategy employed in this work may be a good way to express small-molecule peptides directly in the Pichia pastoris system. Graphical abstract: